(3gOGjI GdeIs - (3GdYGedj, GdoMQ, GdMQ GdYGedj, eMeO Hf GdMSf Hf Ydj, J (B1104(3g` (B1692(3es
(3ChdgG (B:s
(3ChdgG(B: (3HSe Gddg hGddg CcHQ, hQhj EPG QcH GdQLd GdOGHI aSnqei QOag edc jMaXg MJi jfRd, hQhj jbQC BjI GdcQSj hjSJZaQ hjSHM SHYG hjMeO SHYGs
(3BNQgG (B:s
(3BNQgG(B: (3SFd GdHGbQ Ydjg GdSdGe Yf QLd SGaQ hJQc YfO GeQCJg fabI SJI CTgQ Ch fMh Pdc Ke eGJ HYO TgQ Gh GKfjf? bGd(B: (3JQO eG aVd YfOgG aj GdejQGKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 90s
(3GdPQjYI, L (B25: 107s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis